Reclassification of Two MLH1 Variants of Uncertain Significance Utilizing Clinical and Functional Data - Jane Hübertz Frederiksen; Ulf Birkedal; Sarah Bachmann; Elisabeth Victoria Eliesen; Lene Juel Rasmussen; Katja Venborg Pedersen; Lana Al‐Zehhawi; Susanne E. Boonen; Lotte Krogh; Karina Rønlund; Lise Graversen; Jannie Assenholt; et al. (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Pathogenic variants in the mismatch repair genes are associated with an elevated lifetime risk of colorectal cancer (CRC). We previously identified two variants of uncertain significance (VUS) in the MLH1 gene, c.696_698del, p.(Cys233del) and c.1919C > G, p.(Pro640Arg), in Danish families with numerous occurrences of CRC. Methods To reclassify the variants we collected clinical data, initiated tumor and co‐segregation analysis, and performed RNA splicing analysis, subcellular localization, and protein stability studies. Results The functional analysis revealed that the c.696_698del, p.(Cys233del) variant had an effect at the RNA level, on subcellular localization, and on protein stability, while the c.1919C > G, p.(Pro640Arg) variant showed decreased expression in localization studies and decreased protein stability. These results suggest both variants disrupt DNA mismatch repair. Conclusion By applying all collected data and functional results we propose to reclassify the c.696_698del, p.(Cys233del) and the c.1919C > G, p.(Pro640Arg) variants as likely pathogenic (class 4) using MMR gene‐specific ACMG/AMP guidelines. Consequently, the two MLH1 variants can now be used for risk assessment of variant carriers, while family members without the variants can be excluded from intensified cancer surveillance and follow population recommendations.